Testing within Constraints: a Practical Approach - Herbert, Juliana; Nane, Silvia (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2016)
Being able to assure and evaluate system functionality and reliability is essential when we consider the concept of software quality. Although the concept of quality is broader, all the other criteria are secondary if a system fails performing its functions. Software testing is one of the primary methods used in the validation and verification of output in software development industry. However, software testing is considered an expensive process, accounting for as much as 50% of the cost of developing software based systems. Considering this situation, this discipline is often under pressure due time, cost and skills constraints. Although software testing must be optimized, the idea of just adding these constraints affects negatively the effectiveness of the process. The optimization must be done using systematic testing, with the purpose to select reliable test cases. As it is not possible to assure that all the defects of the software under test were identified, it is important to be able to prioritize testing activities. This paper presents a practical approach to test within constraints. Using this approach, the "testing combo", it is possible to define 40 hours testing projects, prioritizing test cases based on the identified risks and on the business value. It is a collaborative approach, where testers and customers work together through daily reports evaluation. The paper also presents a case study where this approach was used in five different projects, in the context of a testing factory.